Atitude estética na formação continuada de professores do ensino fundamental - Moreira, Debora Oliveira (2014)
The present study, located in the Search Line Educational Processes and Language, originated from the desire to bring the aesthetic education of continued education of elementary school teachers, through workshops covering the development of the aesthetic dimension of teachers por meio de construções elaboradas nas estratégias textuais referidas por Mario Gennari (1997). In this context, the objective of this work was to investigate what opportunities offers the development of workshops of aesthetic education for the continuing education of teachers, and which direction they give an aesthetic attitude in education. There are, therefore, the way in which development of workshops of aesthetic education can contribute to the continuing education of teachers and what sense is for them an aesthetic attitude. In order to respond to these questions and other questions raised during the research, we used the qualitative research, by means of which it was possible to check the buildings drawn up on the basis of the workshops of aesthetic education, carried out in meetings continuing education of teachers. The research was carried out by means of participant observation, documented in a field diary, and is based on humanistic paradigm, highlighting, among the major authors that motivated the work, John-San Francisco Duarte Junior (2008; 2001; 1994).The data were analyzed on the basis of the phenomenological method proposed by Giorgi (1985) and Comiotto (1992). This understanding emerged three essences: the aesthetic education in school; languages of art as a form of expression; and interpersonal relationships within the school environment. There were four workshops with a group of teachers of a primary school, a municipality located in the north of the Rio Grande do Sul.The experience has drawn the attention of the teachers regarding the importance of the development of sensitive knowledge, which enables the human being, being in the world, acting in such a way as to transform the reality in which he lives and make the world a better place to live.